1
$\begingroup$

Eliminate $\theta$ from $\lambda \cos2\theta=\cos(\theta + \alpha)$ and $\lambda\sin2\theta=2\sin(\theta + \alpha)$

My approach:

Dividing the RHS and LHS of both equations by $\lambda$, then squaring and adding them, we get, $$\frac{\cos^2(\theta+\alpha)}{\lambda^2}+\frac{4\sin^2(\theta+\alpha)}{\lambda^2}=\cos^22\theta + \sin^22\theta=1$$ $$\Rightarrow \sin^2(\theta+\alpha)=\frac{\lambda^2-1}{3}$$ I am unable to proceed.

$\endgroup$
1
$\begingroup$

We have

\begin{align*} \tan2\theta&=2\tan(\theta+\alpha)\\ \frac{2\tan\theta}{1-\tan^2\theta}&=\frac{2(\tan\theta+\tan\alpha)}{1-\tan\theta\tan\alpha}\\ \tan\theta-\tan^2\theta\tan\alpha&=\tan\theta(1-\tan^2\theta)+\tan\alpha(1-\tan^2\theta)\\ \tan^3\theta&=\tan\alpha \end{align*}

From $\lambda\sin2\theta=2\sin(\theta+\alpha)$,

\begin{align*} 2\lambda\sin\theta\cos\theta&=2(\sin\theta\cos\alpha+\cos\theta\sin\alpha)\\ \lambda&=\frac{\cos\alpha}{\cos\theta}+\frac{\sin\alpha}{\sin\theta}\\ &=\frac{\cos\alpha}{\cos\theta}\left(1+\frac{\tan\alpha}{\tan\theta}\right)\\ \lambda^2&=\frac{\sec^2\theta}{\sec^2\alpha}\left(1+\frac{\tan\alpha}{\tan\theta}\right)^2\\ &=\left(\frac{1+\tan^2\theta}{1+\tan^2\alpha}\right)(1+\tan^2\theta)^2\\ &=\frac{(1+\tan^2\theta)^3}{1+\tan^6\theta}\\ &=\frac{1+2\tan^2\theta+\tan^4\theta}{1-\tan^2\theta+\tan^4\theta}\\ (\lambda^2-1)(1+\tan^4\theta)&=(\lambda^2+2)\tan^2\theta\\ \tan^2\theta+\frac{1}{\tan^2\theta}&=\frac{\lambda^2+2}{\lambda^2-1} \end{align*}

Note that

$$\tan^2\alpha+\frac{1}{\tan^2\alpha}=\tan^6\theta+\frac{1}{\tan^6\theta}=\left(\tan^2\theta+\frac{1}{\tan^2\theta}\right)^3-3\left(\tan^2\theta+\frac{1}{\tan^2\theta}\right)$$

Therefore, $\displaystyle \tan^2\alpha+\frac{1}{\tan^2\alpha}=\left(\frac{\lambda^2+2}{\lambda^2-1}\right)^3-3\left(\frac{\lambda^2+2}{\lambda^2-1}\right)$.

$\endgroup$
2
$\begingroup$

From $\tan^3\theta=\tan\alpha$

$\dfrac{\sin\theta}{(\sin\alpha)^{1/3}}=\dfrac{\cos\theta}{(\cos\alpha)^{1/3}}=\pm\dfrac1{\sqrt{(\cos\alpha)^{2/3}+(\sin\alpha)^{2/3}}}$

From $\lambda\cos2\theta=\cos(\theta+\alpha)$

$$\lambda(\cos^2\theta-\sin^2\theta)=\cos\theta\cos\alpha-\sin\theta\sin\alpha$$

$$\implies\lambda\dfrac{(\cos\alpha)^{2/3}-(\sin\alpha)^{2/3}}{(\cos\alpha)^{2/3}+(\sin\alpha)^{2/3}}=\pm\dfrac{(\cos\alpha)^{1/3+1}-(\sin\alpha)^{1/3+1}}{\sqrt{(\cos\alpha)^{2/3}+(\sin\alpha)^{2/3}}}$$

Assuming $\cos\alpha\ne\sin\alpha,$

$$\lambda=\pm\left((\cos\alpha)^{2/3}+(\sin\alpha)^{2/3}\right)^{1+1-1/2}$$

$$\implies\lambda^{2/3}=(\cos\alpha)^{2/3}+(\sin\alpha)^{2/3}$$

$\endgroup$
  • $\begingroup$ @CYAries, Could you please verify? $\endgroup$ – lab bhattacharjee May 4 at 16:16
  • $\begingroup$ This is beautiful. $\endgroup$ – CY Aries May 6 at 1:24
  • $\begingroup$ It fits the identity I found. But this solution is much better. $\endgroup$ – CY Aries May 6 at 1:35
1
$\begingroup$

Take the square root and then apply $\arcsin$ (odd function) to both sides of the equation. You will obtain

$$\theta = \pm \arcsin \sqrt{\dfrac{\lambda^2-1}{3}}$$ $$\theta = - \alpha \pm \arcsin \sqrt{\dfrac{\lambda^2-1}{3}}$$

Note, that by taking the square root of $\lambda^2-1$ we restrict the possible values of $\lambda$. We have $|\lambda|\geq 1$.

$\endgroup$
  • $\begingroup$ We have been asked to eliminate $\theta$ not to solve for it. This means you need to find a third equation relating all variables except $\theta$ $\endgroup$ – ami_ba May 1 at 17:00
  • 2
    $\begingroup$ After solving for $\theta$ we can remove it in the initial equations. $\endgroup$ – MachineLearner May 1 at 17:02
  • $\begingroup$ @MachineLearner, We have $$\sin^22\theta=\dfrac{4(\lambda^2-1)}{3\lambda^2}$$ then $\theta=?$ $\endgroup$ – lab bhattacharjee May 4 at 15:56
1
$\begingroup$

Result

First we calculate $\theta$

$$\theta = \frac{1}{2} \arcsin\left(\frac{4}{3}(1-\frac{1}{\lambda^2})\right)\tag{1}$$

if $\lambda^2 >1$, and else no solution.

This can be combined with the equation derived in the OP

$$\sin^2(\theta+\alpha)=\frac{\lambda^2-1}{3}\tag{2}$$

to solve for $\alpha$ so that both quantities are eliminated and the equations are completely solved in terms of $\lambda$.

Derivation of (1)

We have

$$ \cos(\theta+\alpha)=\lambda \cos(2 \theta)$$ $$ \sin(\theta+\alpha)=\frac{1}{2}\lambda \sin(2 \theta)$$

so that

$$1 = \lambda ^2 \cos(2 \theta)^2 + \frac{1}{4} \lambda ^2 \sin(2 \theta)^2$$

which eliminates $\alpha$.

Hence, observing $\cos(2 \theta)^2 + \sin(2 \theta)^2 = 1$, follows $(1)$.

$\endgroup$
  • $\begingroup$ We need to eliminate $\theta$ $\endgroup$ – ami_ba May 1 at 17:06
  • $\begingroup$ Thanks for the hint. I have now eliminated both $\theta$ and $\alpha$ and expressed them through $\lambda$, i.e. solved the system completely. $\endgroup$ – Dr. Wolfgang Hintze May 1 at 17:12
  • $\begingroup$ The elimination problem makes more sense if you drop the second equation. You then get an algebraic equation of 8th degree for $\sin(\theta)$. $\endgroup$ – Dr. Wolfgang Hintze May 1 at 17:24

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.